Market exuberance in sovereign credit default swaps: assessing the EU regulatory framework and trading profit opportunities - Oliveira, Maria Alberta (2016)
Sovereign credit default swaps (SCDSs) have been at the core of the Euro Area (EA) debt crisis, particularly in its periphery. Both EU politicians and a wide range of EU academics have asked for tighter regulation of these over-the-counter (OTC) derivatives, following similar pressures to the ones that had resulted from the 2008 financial crisis for corporate reference entities. As such, the SCDSs regulatory framework experienced a number of changes from 2009 to 2014, in the EU. This paper provides a seminal assessment on whether these new rules have succeeded in preventing SCDSs exuberance episodes in the EU. Using daily data for 5 years maturity Greek SCDSs, comprising the period between the latest regulatory reform, in September 2014, and mid-March 2015, we find clear evidence of explosive behavior in SCDSs spreads, and even in upfront quotes. The authors take advantage of the new Phillips et al. (2015a, 2015b) test for multiple exuberance episodes, which had rarely been used in derivatives markets, and conduct an event study to conclude that Greek elections, in early 2015, and the associated turmoil has led to a surge in momentum trading, with significant potential returns for SCDSs buyers. The regulatory measures aiming at deleveraging these markets, standardizing contracts, and dissociating sovereign and banking risk, do not seem to have achieved their purposes, as the political and financial anxiety in Greece, starting in December 2014, has led to explosive behavior episodes in the market for Greek SCDSs, of the type regulators had tried to avoid.